2000
DOI: 10.1002/(sici)1097-4628(20000516)76:7<1011::aid-app4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phase structure on impact toughening of isotactic polypropylene by metallocene-catalyzed linear low-density polyethylene

Abstract: ABSTRACT:In the present study isotactic polypropylene (PP) and metallocene-catalyzed linear low-density polyethylene (mLLDPE) were blended together to obtain thermoplastic materials (compositions) with improved toughness. Structure-property relationships were determined for these compositions with the help of scanning electron microscopy (SEM). Special emphasis was made on tracing the morphological features that led to the optimum mechanical performance. A co-continuous type of structure was found to have much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
4
28
1
Order By: Relevance
“…The number and volume average diameters, D n and D v ; respectively, for the PP/EC 70/30 compositions of both systems, are summarized in Table 4. The particles are generally larger than reported previously for systems with lower viscosity ratios [10,14] and the average diameter of the PP/EOC system is slightly higher. Phase inversion occurs when EBC content is above 50% and EBC becomes the matrix phase at PP/EBC 30/70 composition.…”
Section: Morphology and Mechanical Propertiescontrasting
confidence: 60%
See 1 more Smart Citation
“…The number and volume average diameters, D n and D v ; respectively, for the PP/EC 70/30 compositions of both systems, are summarized in Table 4. The particles are generally larger than reported previously for systems with lower viscosity ratios [10,14] and the average diameter of the PP/EOC system is slightly higher. Phase inversion occurs when EBC content is above 50% and EBC becomes the matrix phase at PP/EBC 30/70 composition.…”
Section: Morphology and Mechanical Propertiescontrasting
confidence: 60%
“…In addition, there are conflicting claims in the literature regarding the miscibility of these blends. Although it seems that in the majority of cases they are thermodynamically immiscible, it has been reported that butene-rich and hexene-rich copolymers are miscible with isotactic PP in the amorphous region [15 -17] and that partial miscibility in blends of PP with ethyleneoctene copolymers may exist at low copolymer contents (below 10%) [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…A further morphological study is being currently undertaken to clarify this conclusion (Part 2). 12 The authors thank the Polymer Technology Centre within RMIT for provision of industrial processing and testing equipment. …”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the main structural type has changed from a dispersed matrix to a co-continuous type with an increasing concentration of the second phase in these systems. 12 From the MDSC results, we can conclude that blends of hcr or conventional PP and mLLDPE with 40%, 50%, and 60% of the latter, appear to be immiscible in the solid state and at temperatures equal and below the melting temperature of PP (165-170°C). However, it has to be emphasized that the apparent immiscibility detected and claimed in the solid state for these compositions is unrelated to immiscibility of these blends at higher temperatures.…”
Section: Changes With Compositions For Conventional Pp/ Mlldpe Blendsmentioning
confidence: 93%
“…In Part I, relations between rheological behavior and thermal and physical properties were analyzed. 1 In this second part, the morphological studies are performed. The structure-property relationships of the "high crystallinity" PP and metallocene-catalyzed linear low density polyethylene blends are examined to verify the applicability of the conclusion made previously 2 about the superiority of a co-continuous structure compared with a matrixdispersed one for blends of conventional PP and metallocene-catalyzed linear low density polyethylene.…”
Section: Introductionmentioning
confidence: 99%